2021
DOI: 10.1155/2021/2370363
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fractal and Energy Consumption Characteristics of Concrete under Impact Loading

Abstract: In order to study the compressive deformation and energy evolution characteristics of concrete under dynamic loading, impact compression tests with impact velocities of 5, 6, and 7 m/s were carried out on concrete samples with aggregate volume ratios of 0, 32%, 37%, and 42%, respectively, using a split Hopkinson pressure bar test apparatus. The broken concrete pieces after destruction were collected and arranged. The fractal characteristics of fragmentation distribution of concrete specimens with different agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Results showed that the fractal dimension of rock fragmentation and the energy dissipation density increase with the increase in strain rate, and the relationship between them satisfies the power function. Li et al (2021) studied the effects of loading rate and aggregate volume fraction on the fractal fracture characteristics of concrete through SHPB experiments and established the analytical expressions of fragmentation fractal dimension and crack surface energy on the basis of fracture theory. Results indicated that the fractal dimension, energy dissipation in fragmentation and crack surface energy increase with the increase in impact velocity and decrease with the increase in aggregate volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the fractal dimension of rock fragmentation and the energy dissipation density increase with the increase in strain rate, and the relationship between them satisfies the power function. Li et al (2021) studied the effects of loading rate and aggregate volume fraction on the fractal fracture characteristics of concrete through SHPB experiments and established the analytical expressions of fragmentation fractal dimension and crack surface energy on the basis of fracture theory. Results indicated that the fractal dimension, energy dissipation in fragmentation and crack surface energy increase with the increase in impact velocity and decrease with the increase in aggregate volume ratio.…”
Section: Introductionmentioning
confidence: 99%